Blocking of snow/water slurry flow in pipeline caused by compression-strengthening of snow column - Shirakashi, Masataka (MDPI AG, 2014)
In earlier works by the present authors, two systems for sustainable energy were proposed: (i) a system for urban snow removal in winter and storage for air conditioning in summer, applied to Nagaoka City, which suffers heavy snow fall every winter, and (ii) a district cooling system utilizing latent heat of ice to reduce the size of storage reservoir and transportation pipeline system. In these systems, the hydraulic conveying of snow or ice through pump-and-pipeline is the key technique to be developed, since characteristics of snow (ice)/ water slurry is largely different from those of conventional non-cohesive solid particle slurries. In this study, the blocking of pipeline of snow/water slurry is investigated experimentally. While the blocking of conventional slurry occurs due to deposition of heavy particles at low flow velocity or arching of large rigid particles, that of snow/water slurry is caused by a compressed plug of snow formed due to cohesive nature of snow particles. This is because the strength of snow plug formed at a high resistance piping element, such as an orifice, becomes higher when the compression velocity is lower, resulting in a solid-like plug filling the whole channel upstream the element